Classroom Promotion of Oral Language (CPOL): protocol for a cluster randomised controlled trial of a school-based intervention to improve children's literacy outcomes at grade 3, oral language and mental health. Issue 11 (20th November 2017) - Goldfeld, Sharon; Snow, Pamela; Eadie, Patricia; Munro, John; Gold, Lisa; Le, Ha N D; Orsini, Francesca; Shingles, Beth; Lee, Katherine; Connell, Judy; Watts, Amy
Abstract : Introduction: Oral language and literacy competence are major influences on children's developmental pathways and life success. Children who do not develop the necessary language and literacy skills in the early years of school then go on to face long-term difficulties. Improving teacher effectiveness may be a critical step in lifting oral language and literacy outcomes. The Classroom Promotion of Oral Language trial aims to determine whether a specifically designed teacher professional learning programme focusing on promoting oral language can lead to improved teacher knowledge and practice, and advance outcomes in oral language and literacy for early years school children, compared with usual practice. Methods and analysis: This is a two-arm cluster multisite randomised controlled trial conducted within Catholic and Government primary schools across Victoria, Australia. The intervention comprises 4 days of face-to-face professional learning for teachers and ongoing implementation support via a specific worker. The primary outcome is reading ability of the students at grade 3, and the secondary outcomes are teacher knowledge and practice, student mental health, reading comprehension and language ability at grade 1; and literacy, writing and numeracy at grade 3. Economic evaluation will compare the incremental costs of the intervention to the measured primary and secondary outcomes. Ethics and dissemination: This trial was approved by the Monash University Human Research Ethics Committee #CF13/2634-2013001403 and later transferred to the University of Melbourne #1545540. The investigators (including Government and Catholic partners) will communicate trial results to stakeholders, collaborators and participating schools and teachers via appropriate presentations and publications. Trial registration number: ISRCTN77681972 ; Pre-results.